Experimental Study on Panchanan Rasa w.s.r. to its Acute Oral Toxicity (International Journal of Ayurveda and Pharma Research, 2023)
Ras sashtra is a specialized branch of Indian traditional system and medicine which deals with metals, minerals, herbal compounds, and various principles of alchemy and metallurgy etc. Panchanan Rasa chief reference is in Ras Ratna Sammuchya Hridya Roga Chikitsa for Hridya Roga. It is a herbo-mineral preparation made with the help of Kharal so called Kharaliya preparation and is used in powder form to be given to patient. In present era Hridya Roga is becoming a common problem, every one person in ten people is suffering from CAD/IHD with varied etiology and is going under long term medication, costly surgeries which every patient is not able to afford, so this article discuss about the acute oral toxicity of Panchanan Rasa and found it non-toxic on Albino rats.